Neither) companions (nor) revolutionaries. The representation of women in poetry 2.0 - Lamora Aranda, Lucía (Filanderas, 2021)
The production, dissemination, and enjoyment of the poetic experience have changed considerably in recent years. The primary factor that has caused this revitalization of poetry is the internet, and more specifically, social media. The evolution of poetry towards new digital avenues has been motivated by the incorporation of the millennial generation into the artistic market, an audience that did not consider the lyrical genre within their interests. One of the consequences of this revolution is the democratization of poetry. The new forms of production and of reception have made it so the concepts of author-writer-reader no longer reflect the same schemata to which lyrical poetry was fitted just a few years ago. From this perspective, in the current study we will focus on analyzing how the image of women is developed in the discourse of two poets who hold first place in this new poetic «canon» of the twenty-first century in Spain: Marwan and Diego Ojeda. Based on the analysis, we intend to respond to the question that makes up the central idea of this work: Has the stereotype regarding the representation of women in poetry 2.0 been updated? The critical analysis from the text «Compañeras» and «Mi chica revolucionaria» (added to the Anexo I) shows chauvinism perpetuity hidden within digital vortex.
Keywords: Female Representation; Poetry 2.0; Ciberpoets; Social Media; Democratization